Socioeconomic differences in prevalence, awareness, control and self-management of hypertension among four minority ethnic groups, Na Xi, Li Shu, Dai and Jing Po, in rural southwest China - Cai, L; Dong, J; Cui, W L; You, D Y; Golden, A R (Journal of human hypertension, 2017)
This study investigates socioeconomic differences in prevalence, awareness, control and self-management of hypertension in rural China. A cross-sectional survey was conducted among four ethnic minority groups in Yunnan Province: Na Xi, Li Shu, Dai and Jing Po. Approximately 5532 consenting individuals aged ⩾35 years (48.4% of whom were male) were selected to participate in the study using a stratified, multistage sampling technique. Information about participants’ demographic characteristics and hypertension awareness, treatment, control and self-management practices was obtained using a standard questionnaire. The age-standardised prevalence of hypertension in the study population was 33.6%. In hypertensive subjects, the overall levels of awareness, treatment and control of hypertension were 42.1%, 28.5% and 6.7%, respectively. Approximately 58.7% of hypertensive patients regularly self-monitored blood pressure (BP), 64.7% adhered to their physician-prescribed anti-hypertensive drugs, and 88.0% took at least one measure to control BP. Hypertensive patients of Jing Po ethnicity had the lowest rates of awareness, treatment, control and self-management of hypertension among the four ethnic minority groups studied. Individuals with lower levels of education were more likely to be hypertensive. Further, individuals with lower levels of education had a lower probability of awareness of their hypertensive status and of treatment with antihypertensive medication. Access to medical services was positively associated with awareness of suffering from hypertension, being treated with antihypertensive medication, and compliance with antihypertensive drug treatment. This study suggests that effective strategies to enhance awareness, treatment and management of hypertension should focus on individuals with low levels of education and poor access to medical services.